2011
DOI: 10.1007/s11274-011-0805-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a strain of Aspergillus fumigatus able to grow in minimal medium added with an industrial cyanide waste

Abstract: The present note refers the results about the isolation of an Aspergillus fumigatus strain able to grow on an industrial cyanide waste as nitrogen source. The fungus was selected from an alkaline unpolluted soil in enrichment cultures in 50 ml of Minimal Medium added with 20 mmol glucose and supplemented initially with 0.1 mmol KCN and then with 70 μl of a waste solution from a jewelry industry containing free cyanide and cyanide complexes of heavy metal ions including copper, silver, nickel, and others. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…LB medium: 10.0 g/L peptone, 5.0 g/L yeast extract, 10.0 g/L NaCl. Minimal medium: 20.0 g/L glucose, 1.0 g/L yeast extract, 6.8 g/L Na 2 HPO 4 ·7H 2 O, 3.0 g/L KH 2 PO 4 , 0.5 g/L NaCl, 0.01 g/L CaCl 2 , 1 mL of trace metal solution (H 3 BO 3 30 mg/L; CoCl 2 ·6H 2 O 200 mg/L; ZnSO 4 ·7H 2 O 100 mg/L; MnCl 2 ·4H 2 O 10 mg/L; pH 6.0) and increasing content of cyanide (25 mg/L, 100 mg/L, 200 mg/L), pH 8.0 [ 24 ]. Glucose inorganic salt medium (GI): 50.0 g/L glucose, 10.0 g/L peptone, 5.0 g/L (NH 4 ) 2 SO 4 , 2.0 g/L KH 2 PO 4 , 1.0 g/L MnCl 2 , 5.0 g/L NaCl, pH 7.0–7.2.…”
Section: Methodsmentioning
confidence: 99%
“…LB medium: 10.0 g/L peptone, 5.0 g/L yeast extract, 10.0 g/L NaCl. Minimal medium: 20.0 g/L glucose, 1.0 g/L yeast extract, 6.8 g/L Na 2 HPO 4 ·7H 2 O, 3.0 g/L KH 2 PO 4 , 0.5 g/L NaCl, 0.01 g/L CaCl 2 , 1 mL of trace metal solution (H 3 BO 3 30 mg/L; CoCl 2 ·6H 2 O 200 mg/L; ZnSO 4 ·7H 2 O 100 mg/L; MnCl 2 ·4H 2 O 10 mg/L; pH 6.0) and increasing content of cyanide (25 mg/L, 100 mg/L, 200 mg/L), pH 8.0 [ 24 ]. Glucose inorganic salt medium (GI): 50.0 g/L glucose, 10.0 g/L peptone, 5.0 g/L (NH 4 ) 2 SO 4 , 2.0 g/L KH 2 PO 4 , 1.0 g/L MnCl 2 , 5.0 g/L NaCl, pH 7.0–7.2.…”
Section: Methodsmentioning
confidence: 99%
“…This occurs most often from nitriles or free cyanide; however, metal-complexed cyanide has also been reported to be attenuated biologically, but in most studies, it is difficult to determine whether the attenuation was by direct utilization of the complex or by utilization of free cyanide released by complex dissociation (JOHNSON, 2015). (SABATINI et al, 2012). These studies have shown that microbes adapt to hostile environments and therefore, cyanide-degrading species can be isolated from cyanide-containing wastes and they could be adapted to toxic concentrations as high as the one present in the waste from which they were adapted.…”
Section: Applied Biotechnology For Cyanide Treatmentmentioning
confidence: 99%